Factors Associated with the Risk of Musculoskeletal Disorders Complaints among Staff Nurses at RSUD dr. Doris Sylvanus - Syabriannur M; Husaini Husaini; Lenie Marlinae; Triawanti Triawanti; Harapan Parlindungan Ringoringo (An-Nadaa : Jurnal Kesehatan Masyarakat (e-Journal), 2025)
Abstract                                                                                  This research examines factors associated with the risk of musculoskeletal disorders (MSDs) complaints among staff nurses at dr. Doris Sylvanus Palangkaraya Hospital. The objective is to determine the relationships between age, gender, length of employment, work posture, physical workload, and work fatigue with the risk of MSD complaints. An analytical observational method was employed, utilizing bivariate analysis through the Chi-square test and multivariate analysis using multiple logistic regression. Bivariate analysis revealed significant associations for length of employment (p = 0.005; odds ratio [OR] = 12.833) and work posture (p = 0.029; OR = 7.333). No significant associations were found for age (p = 0.088; OR = 4.680), gender (p = 1.000; OR = 0.900), physical workload (p = 0.703; OR = 1.400), and work fatigue (p = 0.098; OR = 4.667). Multivariate analysis identified length of employment as the most dominant factor (Exp(B) = 12.833). In conclusion, length of employment is the most influential factor in the risk of MSD complaints among staff nurses at Dr. Doris Sylvanus Palangkaraya Hospital. It is recommended to implement periodic non-communicable disease (NCDs) screening programs, particularly for MSD complaints among nurses, optimize hospital occupational safety and health management systems (SMK3RS) and promote self-stretching exercises among healthcare workers.Keywords: Musculoskeletal disorders; nurses; working posture; physical workload; work fatigue